1996
DOI: 10.1002/j.1460-2075.1996.tb00707.x
|View full text |Cite
|
Sign up to set email alerts
|

pX, the HBV-encoded coactivator, interacts with components of the transcription machinery and stimulates transcription in a TAF-independent manner.

Abstract: The X protein of hepatitis B virus (HBV) coactivates activators bearing potent (mostly acidic) activation domains. Here, we investigated the molecular mechanisms of this coactivation. We show that pX interacts with general transcription factors TFIIB and TFIIH, as well as with the potent activation domain of VP16. TFIIB interacts with both pX and VP16 simultaneously. In addition, the RNA polymerase II enzyme itself binds to pX. By reducing the activity of cellular coactivators, through squelching, we intensify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 61 publications
6
105
0
Order By: Relevance
“…Therefore an obvious question is how the HBx-RPB5-TFIIB trimeric interaction enables promoter selectivity in HBx transactivation. HBx alone does not transactivate the pGal4-CAT reporter but facilitates the activation of Gal4-VP16, suggesting that HBx acts during activated, but not basal transcription (33,63). 3 In this regard, HBx may directly or indirectly communicate with some transcriptional activators (19,20).…”
Section: Hbx Rpb5 and Tfiib May Form A Ternary Complex-mentioning
confidence: 99%
“…Therefore an obvious question is how the HBx-RPB5-TFIIB trimeric interaction enables promoter selectivity in HBx transactivation. HBx alone does not transactivate the pGal4-CAT reporter but facilitates the activation of Gal4-VP16, suggesting that HBx acts during activated, but not basal transcription (33,63). 3 In this regard, HBx may directly or indirectly communicate with some transcriptional activators (19,20).…”
Section: Hbx Rpb5 and Tfiib May Form A Ternary Complex-mentioning
confidence: 99%
“…Similarly, the cellular pathways targeted by the viral protein to achieve transcriptional transactivation are a matter of debate. Indeed, in several studies, X has been reported to directly act on the transcriptional machinery (Cheong et al, 1995;Haviv et al, 1996;Lin et al, 1998;Maguire et al, 1991). In others, X appears to act far more upstream, by modulating the signal transduction cascade in the cytoplasm (Benn et al, 1996;Chirillo et al, 1996;Henkler et al, 1998;Kekule et al, 1993;Klein and Schneider, 1997;Lee and Yun, 1998;Su and Schneider, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…7,8,25,36 The likelihood that HBxAg mediates these alterations in cell behavior by binding to a variety of cellular proteins, including members of the transcriptional machinery, 16,18 one or more molecules involved in DNA repair, 21,37 a subunit of the proteasome, 38 and the tumor-suppressor protein p53, 19 point to some of the putative molecular pathways that may be relevant to the development of this tumor type. Given the complexity of growth control, and that carcinogenesis is a multistep process, it is likely that HBxAg may bind to and alter the function of other growth-regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%